Evaluating the optimality of Spanish industry (1980-1993) - Rosina Moreno; Enrique Lopez-Bazo; Manuel Artis (European Regional Science Association (ERSA), 2002)
This paper tests whether Spanish industry adjusted the amount of inputs and output to those considered optimal given their prices in each time period. With this aim, we use the short- and long-run equilibrium models given by duality theory, and we apply the optimality tests derived from them for the case of Spanish manufactures from 1980 to 1993. The results obtained point to a disequilibrium in manufactures' behaviour, although it has been vanishing through the period under consideration.
Keywords: 330